2019
DOI: 10.3389/fnagi.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the SNCA Locus Are Associated With the Progression of Parkinson's Disease

Abstract: Background: Genetic factors have a well-known influence on Parkinson's disease (PD) susceptibility; however, no previous studies have investigated the influence of SNCA mutations on the natural history of PD using a prospective follow-up study. The aim of this study was to assess the risk factors of variation of SNCA on the prognosis symptoms of PD patients. Methods: Fifty PD patients were recruited with 38 v-PSG confirmed PD+RBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…No differences between genotype groups and the annual change in MMSE score were observed for the control subjects over the same follow-up period, indicating that this effect is disease-specific. Similar to our findings, Luo et al ( 21 ) found an association between the rate of cognitive impairment and rs356219. However, in their study of patients with PD from China, carriers of the G-allele had a decreased risk of cognitive decline, indicating that the G allele might have a protective role in this population ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No differences between genotype groups and the annual change in MMSE score were observed for the control subjects over the same follow-up period, indicating that this effect is disease-specific. Similar to our findings, Luo et al ( 21 ) found an association between the rate of cognitive impairment and rs356219. However, in their study of patients with PD from China, carriers of the G-allele had a decreased risk of cognitive decline, indicating that the G allele might have a protective role in this population ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, Luo et al ( 21 ) found an association between the rate of cognitive impairment and rs356219. However, in their study of patients with PD from China, carriers of the G-allele had a decreased risk of cognitive decline, indicating that the G allele might have a protective role in this population ( 21 ). In an analysis of European patients with PD, Goris et al reported no association of rs356219 with the annual change in MMSE ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Fourteen studies including a total of 31 different polymorphisms used the H&Y scale to measure PD severity (Supplementary Table 3 ), but the means by which the scale was used varied widely. For example, Davis et al report no significant association between rs356219 or rs11931074 and the annual change in H&Y stage 22 , while in other studies these same SNPs were shown to be significantly associated with either a longer time to a 0.5-point increase in H&Y stage (rs356219; HR 0.20; p = 0.005) 37 or a longer time to reach H&Y stage ≥3 (mild-to-moderate disability) (rs11931074; HR 0.43; p = 0.03) 31 . Similarly, REP1 score was reported to be associated with a longer time to reach H&Y stage ≥4 (severe disability) (HR 0.87; p = 0.046) 38 , while reports on the association of the REP1 polymorphism with H&Y stage at the time of examination are conflicting 34 , 36 .…”
Section: Resultsmentioning
confidence: 95%
“…In the most comprehensive assessment of cognitive performance and rs356219, Mata et al analyzed global cognitive function using the Montreal Cognitive Assessment (MoCA), and memory; attention and executive function; language processing; and visuospatial skills in 1079 patients with PD of European descent and found no significant association between rs356219 and any outcome 40 . Two small studies did show a significant association of rs356219 with global cognitive impairment, with conflicting results: in a Chinese explorative study of 50 patients, the rs356219-G allele was significantly associated with an 18% decreased risk of cognitive decline ( p = 0.006), measured by the time to a 1-point decrease on the MoCA scale 37 . Conversely, a Brazilian study of 105 patients found that both rs356219 heterozygotes (rs356219-GA; OR 4.74; p = 0.021) and homozygotes (rs356219-GG; OR 5.74; p = 0.014) had significantly increased risk of cognitive impairment as defined by an education-corrected Mini-Mental State Examination (MMSE) cut-off 35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation